Implications of physicians and nurses’ professional satisfaction on patient care - Wilson Kipkirui Aruasa; Linus Kipkorir Chirchir; Stanley Kulei Chebon (International Journal of Public Health Science (IJPHS), 2019)
The patient outcomes of a health organization depend on the knowledge, skills and motivation of its individual employees. Therefore, it is important for health care employers to motivate their workers in order to meet the desired outcomes. It is widely acknowledged that health workers who are motivated facilitate the desired patient outcomes. This illustrates how the levels of physicians’ and nurses’ professional satisfaction influences the health care outcomes for patients based on a study of the Moi Teaching and Referral Hospital (MTRH). Descriptive quantitative research design was used. Data was collected using a structured questionnaire issued to a stratified group of 82 Physicians and 220 Nurses. All the completed questionnaires were entered into IBM SPSS 21.0 statistical software and data analysed for descriptive statistics. The results were presented in tables and figures. The study was powered to 95% confidence interval. With regards to effects of general practitioners’ and nurses’ work satisfaction on patient services, the study revealed that work associated with the respondents’ position allows contributions to be made to the hospital, the profession and to own sense of achievement. Furthermore, the study findings showed that praise received for work well done translates to improved job productivity and that the medicine/nursing practice allows autonomous professional decisions to be made which in turn promotes high levels of clinical competence. Based on these findings, the study concludes that health care practitioners’ work satisfaction has implications on patient care.